Semantica ed etimologia dell’armeno hnjan ‘vasca in cui si preme l’uva’ (Atti del Sodalizio Glottologico Milanese, 2021)
The article deals with the Armenian substantive hnjan, which in the modern language denotes the ‘wine-press’ or a ‘rural hut located on the fields’. An exam of its use in the texts of classical age where it is attested (the translation of the Bible and the History of Armenians of Agathangelos) allows to recognize an original meaning of ‘hole dug for the squeezing and the fermentation of the grapes’. The etymology proposed connects the word with Sanskrit paṅka- ‘mud, mire, dirt, clay; ointment; moral impurity’, and a German cognate represented by Old High German fūhti, fūht, Anglo-Saxon fūht ‘damp, moist’, the German source of the Romance loanwords Italian, fango, French fange, Catalan fanc ‘mud, mire’.
Keywords: Armenian; Viticulture; Etymology; Indo-European Historical Phonology